Given the equation below ( is the parameter):
We find that a solution to this equation is . Find another real solution of this equation and . Type
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
This quadratic simply factors into:
x 2 − ( m − 1 ) x − m = ( x + 1 ) ( x − m ) = 0 ⇒ x n = − 1 , m = 2 .
Thus, x n + m = 1 .